KESETARAAN GENDER DALAM PEMBANGUNAN PERTANIAN - Setiawan, Eko (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
The issue of gender equality is mainly reflected in terms of access to opportunities and possibilities, participation in decision-making processes, control of resources and benefits from agricultural development outcomes. Women's traditional rights, including children's rights, are not diminished due to the utilization of agricultural natural resources and their products. Equality of access of women and men to information on the use of capital, agricultural facilities and infrastructure must also continue to be fought. The purpose of writing this article is to analyze the concept of gender in wages and the division of agricultural labor and the role of women in agricultural development. Using literature study research, in the form of a series of activities related to library data collection methods, reading and recording, and managing research materials. Data collection comes from textbooks, national and international online journals, scientific articles, literature reviews containing the concept of gender in agricultural development. The results showed that development in agriculture, the role of women tends to be less meaningful and gender inequality occurs. This also applies to agriculture, where women are given